RAGAM HIAS NISAN PASSULARA KONYINA KABALLANGAN DI DESA KABALLANGAN KECAMATAN DUAMPANUA KABUPATEN PINRANG - Nur Hidayah; Ishak Kadir; Sandy Suseno (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The purpose of this research is to identify the elements of ornamental variety and cultural elements that influence the gravestones in the Passulara Konyina Kaballangan Cemetery Complex in Kaballangan Village, Duampanua District, Pinrang Regency. The research method employed is descriptive analysis, consisting of several stages such as literature review, observation, interviews, and documentation. In analyzing the data, this study uses morphological and stylistic approaches. Based on the research findings, the decorative motifs on the gravestones in the Passulara Konyina Kaballangan Cemetery Complex include geometric patterns, floral designs, and inscriptions in Arabic and Lontara scripts. The forms and decorative elements identified in these two types of graves indicate the presence of megalithic culture, local traditions, and Islamic culture, which have developed in the Pinrang area.